Experimental Investigation of Steady and Unsteady Flow Field Downstream of an Automotive Torque Converter Turbine and Stator - B. V. Marathe; B. Lakshminarayana (International Journal of Rotating Machinery)
The objective of this investigation is to understand the steady and the unsteady flow field at the exit of an automotive torque converter turbine and stator with a view towards improving it's performance. A high frequency response five-hole probe was designed and built to measure the three-dimensional steady and unsteady flow fields. The measurements were conducted in a stationary frame of reference and the data were processed to derive the flow properties in the relative (turbine) frame of reference. The experimental data were processed in the frequency domain by spectrum analysis and in temporal-spatial domain by ensemble averaging technique. The data show that the flow field is highly unsteady with high unresolved unsteadiness (approx. 17-21% of mean value) and significant blade-to-blade periodic component approx. 6% of mean value). The unresolved unsteadiness and periodic unsteadiness increase with an increase in the radius from the shell to the core whereas the aperiodic unsteadiness does not show any systematic variation with the radius. The experimental data reveal the presence of a low momentum region near the core due to possible flow separation and reattachment inside the turbine passage. Data also show the presence of strong secondary flow near the core and weak secondary flow near the shell at the exit of the turbine. These secondary flows generate high levels of turbulence. A comparison of the flow properties upstream and downstream of the stator in the stationary frame of reference indicate the presence of high losses near the core due to high turbulence levels and large secondary flows, and high losses near the shell due to possible corner separation near the shell suction surface inside the stator blade passage. The unsteadiness in the flow properties upstream of the stator is high. The rms value of the unsteady total velocity is approx. 20% of the steady state value. Periodic and aperiodic unsteadiness were also found significant.